Verruciform xanthoma of the oral mucosa. Report of four cases and a review of the literature - Oliveira, P. T.; Jaeger, R. G.; Cabral, LAG; Carvalho, Y. R.; Costa, ALL; Jaeger, MMM (Elsevier B.V., 2001)
We present four new cases of verruciform xanthoma (VX) in the oral mucosa and review the literature. Clinical, histological, and immunohistochemical features of four new cases of VX were analysed together with cases found in a review of the literature. Expression of CD-68 was studied by immunohistochemistry. Only 162 cases were reported in the oral mucosa. Ninety were males (55.5%) and 72 were females (44.5%). Mean age was 44.9 years. The majority of cases occurred in masticatory mucosa (69.7%). Our cases exhibited papillary or verrucous proliferation of squamous epithelium associated with hyperparakeratosis and with numerous foamy cells confined to the lamina propria papillae. Foamy cells were positive to CD-68 antibody, showing a macrophagic nature. VX is a rare benign lesion, and is probably inflammatory. However, its aetiology and pathological mechanisms remain unknown. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: verruciform xanthoma; oral mucosa; immunohistochemistry